Temporal trends in the contribution of Chagas cardiomyopathy to mortality among patients with heart failure. Issue 18 (9th March 2018) - Nadruz, Wilson; Gioli-Pereira, Luciana; Bernardez-Pereira, Sabrina; Marcondes-Braga, Fabiana G; Fernandes-Silva, Miguel M; Silvestre, Odilson M; Sposito, Andrei C; Ribeiro, Antonio L; Bacal, Fernando; Fernandes, Fabio; Krieger, Jose E; Mansur, Alfredo J; et al.
Abstract : Background: Chagas cardiomyopathy (ChC) prevalence is decreasing in Brazil and medical therapies for heart failure (HF) have improved in the last decade. Whether these changes modified the prognosis of ChC relative to non-Chagas cardiomyopathies (NChC) remains unknown. This study evaluated the temporal trends in population attributable risk (PAR) of ChC for 2-year mortality among patients with HF enrolled at years 2002–2004 (era 1) and 2012–2014 (era 2) in a Brazilian university hospital. Methods: We prospectively studied 362 (15% with ChC) and 582 (18% with ChC) HF patients with ejection fraction ≤50% in eras 1 and 2, respectively and estimated the PAR of ChC for 2-year mortality. Results: There were 145 deaths (29 in ChC) in era 1 and 85 deaths (26 in ChC) in era 2. In multivariable Cox-regression analysis adjusted for age, sex, ejection fraction, heart rate, body mass index, hypertension, diabetes mellitus, systolic blood pressure and ischaemic/valvar aetiology, ChC was associated with higher risk of death in era 1 (HR (95% CI)=1.92 (1.00 to 3.71), p=0.05) and era 2 (HR (95% CI)=3.51 (1.94 to 6.36), p<0.001). In fully adjusted analysis, the PAR of ChC for mortality increased twofold from era 1 (PAR (95% CI)=11.0 (2.8 to 18.5)%) to era 2 (PAR (95% CI)=21.9 (16.5 to 26.9)%; p=0.023 versus era 1). Conclusion: Although the absolute death rates decreased over time in the ChC and NChC groups, the PAR of ChC for mortality increased among patients with HF, driven by increases in the HR associated with ChC. Our results highlight the need for additional efforts aiming to prevent and treat ChC.